ACCOUNTING RESEARCH: OBJECTIVES AND METHODS. - Sanders, T. H. (The Accounting Review, 1940)
Abstract According to the author of this article, it is not his purpose to deal at length with the materials or subject matter with which accounting research might concern it. While some mention will be made of these materials, he is more concerned to develop certain points of view, which he thinks should animate the research worker in accounting. A common assertion by research workers is that a given generally accepted principle ought to be re-examined, or that indeed all of them ought to be re-examined. This is a proposition, which in itself can receive general consent. But it often happens that the statement "that generally accepted principles of accounting should be re-examined" is frequently made by those who already have rather definite ideas for converting those generally accepted principles into something entirely different from what they are, or were ever intended to be. Those accountants who pretend to anything at all along the lines of accounting research cannot ignore the idea which bobs up from time to time, that accountants should try to devise a presentation of their data in entirely new forms.